Impacts of export tax of cocoa beans on Indonesian economy. - Yuventus Effendi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
In  recent  years,  there  is  a  significant  decline  of  cocoa  beans  in  terms  of exports  value  and  share  after  2010.  Several  studies  claimed  that  this  downward trend  was  caused  by  the  introduction  of  an  export  tax  on  cocoa  beans  in  2010. Nevertheless, there are limited studies on the impacts of decreasing cocoa beans exports to  the  Indonesian  economy.  Therefore,  this  study  aimed  to  simulate  the impacts  of  the  imposition  of  export  tax  on  cocoa  beans  to  the  economy  as  well as  unemployment.  Methodology  of  this  study  utilised  the  Input-Output  Table. In  particular,  this  study  calculated  the  impacts  of  export  tax  on  cocoa  beans  to the  changes  of  output,  primary  inputs,  and  unemployment  in  several  scenarios. The main result of this study was that at extreme scenario, where the cocoa beans sector’s  export  was  eliminated,  the  impacts  on  the  whole  economy  and  unemployment were  insignificant.  Moreover,  this  study  found  that  the  impacts  on  value added  such  as  decreasing  of  profit  were  relatively  higher  than  decreasing ra te  on the  output  and  others  value  added  such  as  salary  and  wages  and  indirect taxes. On  the  other  hand,  this  study  argued  that  even  though  the  introduction  of  export tax  effectively  reduced raw  cocoa  beans  exports,  there  was  an  increasing  on  the exports’  value on the  down  stream  industries.